A bibliometric and knowledge-map study on the treatment of hematological malignancies with CAR-T cells from 2012 to 2023 - Qing Huang; Huimin Li; Yuan Zhang (Taylor & Francis Group, 2024)
Recently, CAR-T cell therapy in hematological malignancies has received extensive attention. The objective of this study is to gain a comprehensive understanding of the current research status, development trends, research hotspots, and emerging topics pertaining to CAR-T cells in the treatment of hematological malignancies. Articles pertaining to CAR-T cell therapy for hematological malignancies from the years 2012 to 2023 were obtained and assessed from the Web of Science Core Collection (WoSCC). A bibliometric approach was employed to conduct a scientific, comprehensive, and objective quantitative analysis, as well as a visual analysis, of this particular research domain. A comprehensive analysis was conducted on a corpus of 3643 articles, which were collaboratively authored by 72 countries and various research institutions. CAR-T cell research in treating hematological malignancies shows an increasing trend each year. Notably, the study identified the countries and institutions displaying the highest level of activity, the journals with the most citations and output, as well as the authors who garnered the highest frequency of citations and co-citations. Furthermore, the analysis successfully identified the research hotspots and highlighted six emerging topics within this domain. This study conducted a comprehensive exploration and analysis of the research status, development trends, research hotspots, and emerging topics about CAR-T cells in the treatment of hematological malignancies from 2012 to 2023. The findings of this study will serve as a valuable reference and guide for researchers seeking to delve deeper into this field and determine the future direction of their research.